Subcritical crack growth in hard alloys under cyclic loading. Issue 2 (8th October 2020) - Brackmann, Lukas; Röttger, Arne; Weber, Sebastian; Theisen, Werner
Abstract: In this work, the subcritical crack growth in Fe‐, Ni‐ and Co‐base hard alloys was investigated. Specimens were cyclically loaded in the pressure threshold range until a ring crack resulted as a failure criterion. Crack propagation along with the individual microstructural constituents and the associated resistance of the individual materials to crack propagation was investigated by scanning electron microscopy and by the methods adapted to it. For the Ni‐base alloys, the formation of a closed ring fracture occurred after the lowest load cycle number, followed by the Co‐ and Fe‐base alloys. Almost no crack deflection by the hard phases was detected in the Ni‐base alloys. The higher number of loading cycles to produce a closed crack ring in the Fe‐base alloys is attributed to the pronounced crack deflection by the hard phases and to the higher matrix strength. Besides, phase transformations were registered in front of the crack tip of the Co‐ and the partially austenitic Fe‐base alloy. This phase transformation counteracts crack formation in the case of the Fe‐base matrix but promotes crack propagation in the Co‐base alloy.